The Role of Supervision in Curriculum Implementation in Educational Units - Lyadi, Muslim; Syarif, Syarif; Syaifuddin, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Teachers are an integral part of any curriculum development process. as a component of the organizing, planning and assessment process. By creating a successful curriculum, teachers assume full responsibility for the learning process that takes place in the classroom. Therefore, it is hoped that every educator understands the importance of monitoring education in the teaching and learning process to help improve the quality of education. This research aims to find out the role of supervision in the learning curriculum. Does it have a good impact on the quality of education at school? This research is library research, namely research that uses literature (libraries) in the form of books, notes and reports of previous research results. The results of the research show that curriculum supervision is seen as a planned and organized system consisting of elements that influence achievement. learning objectives that have been set. Curriculum monitoring requires current input, background, procedures and approaches as a system. Because component criteria are always influenced by time, money, and effort, they must be chosen carefully. Each of the identified elements must be connected to each other and work together to make educational curriculum oversight successful. The role of curriculum supervision is very important for educational progress, especially in the learning process.